Perancangan Sentra Wisata Kuliner di Nusa Penida, Kabupaten Klungkung, Bali - Razani, Amirah; Oka Saraswati, Anak Agung Ayu; Suryada, I Gusti Agung Bagus (Jurnal Arsitektur Universitas Udayana, 2021)
The development of Sampalan port that will be the only one access to Nusa Penida will makes the area around the Sampalan more developed in tourism aspect in a couple of years. Nusa Penida which has nature potential also has local food that has not been widely known. Crop yields in Nusa Penida like cassava, maize, and nuts can be processed to make local foods. That means there is no need to import food supplies from Denpasar anymore. They are ledok and jukut-jukut. These peculiar foods that are not yet widely known can be a potential of tourist attraction for domestic or foreign tourist. The Sampalan area is the most densely populated area in Nusa Penida District, but currently there is no culinary tour as well as a recreation area that is large enough to accommodate domestic and foreign tourists who come through the Sampalan Port. Therefore there is should be Center of Culinary that able to give natural tourism as well as local food tourism for local or foreign around the Sampalan area.The methods that will be used in this article are design methods and methods of approach. Keyword: center of culinary, culinary , food, design, Nusa Penida